CP-081 Management of uncontrolled blood pressure in patients with multiple drug intolerance referred to a specialist hypertension clinic. (24th March 2015) - Antoniou, S; Hamedi, N; Lidder, S; Saxena, M; Brier, T; Robinson, P; Kapil, V; Lobo, M
Abstract : Background: The management of hypertension in patients with known multiple drug intolerance (MDI) is a fundamental challenge. Our hypertension specialist centre has devised an alternative protocol to standard dosing for patients referred with MDI. This includes use of fractional tablet dosing, liquid formulations and trans-dermal formulations of standard anti-hypertensive (s). Purpose: To assess the effects of an innovative approach to blood pressure (BP) control in patients with known MDI. Material and methods: We retrospectively analysed clinic letters for the first 25 patients with a diagnosis of MDI who had at least 3 clinic visits. Clinic BP and any modification to treatment were extracted. A change in clinic BP from baseline through subsequent visits was analysed. Data are expressed as mean ± Standard deviation. Results: 25 (15 female) patients (mean age 62.1 ± 12.0 years) were intolerant of 6.3 ± 3.6 anti-hypertensive medicines at the first visit with baseline clinic BP of 170 ± 21/98 ± 15 mmHg. Patients had 4.6 ± 1.5 follow-up visits over 1.2 ± 1.0 yrs. Clinic systolic/diastolic BP (SBP/DBP) were reduced compared to baseline over the period of follow-up (p < 0.001, p = 0.05 respectively, table 1 ). Conclusion: Fractional tablet dosing may target multiple physiological pathways but minimise dose-dependent adverse effects. Liquid formulations avoid excipients that may contribute to adverse effects and trans-dermal patches overcome gastro-intestinal intolerance associated with tablets. This is the first dedicated anti-hypertensive protocol for high-risk patients with multiple medicines intolerance and application of our novel strategy. It demonstrated BP control improving consistently over subsequent visits. References and/or Acknowledgements: Chobanian AV, Bakris GL, Black HR, et al . The seventh report of the Joint National Committee on prevention, detection, evaluation, and treatment of high blood pressure. JAMA 2003;289:2560–72 No conflict of interest.